Taking stock: evaluating the conduct of forensic interviews with children in New Zealand. Issue 6 (2nd July 2016) - Wolfman, Missy; Brown, Deirdre; Jose, Paul
ABSTRACT: This study examined adherence to the New Zealand Specialist Child Witness Interviewing model in 93 interviews with children about sexual abuse allegations. Interviewers ( n = 27) demonstrated good adherence to the scripted components of the model during the preparation stage of the interview. When investigating the abuse allegation, interviewers demonstrated a greater use of Direct ('Wh-') (57%), and Option-posing prompts (20%) than stipulated by the model and fewer broad open-ended prompts (22%). Very few suggestive questions were posed. In contrast to recommended practice, Direct and Option-posing prompts were not only asked frequently, but were introduced very early in the investigative phase of the interview. Training, supervision and feedback should focus on increasing the use of broad open-ended prompts and minimizing premature use of more focused prompts to promote best-practice interviews.